Development and Validation of a New Stability Indicating Reversed-phase High‑Performance Liquid Chromatography Method for the Simultaneous Estimation of Tegafur and Uracil in Capsule Dosage Form - Archakam, Sreenivasa Charan (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of this study is to develop a new stability indicating reversed-phase high-performance liquid chromatography (RP-HPLC) method for the simultaneous estimation of Tegafur (TEG) and Uracil (URA) in capsule dosage form. Materials and Methods: Chromatography was carried out on a C18 Phenomenex column (250 mm × 4.6 mm i.d., 5 μm particle size) with an isocratic mobile phase composed of acetate buffer (pH 4) and methanol in the proportion of 70:30 (v/v). The compounds were eluted at a steady flow rate of 1.0 mL/min with a total run time of 10 min. The detection was carried out by ultraviolet-detector at 280 nm. The developed method was validated as per the ICH guidelines, and stability studies were performed. Results and Discussion: TEG retention time was about 5.2 min, and URA was 2.9 min. A calibration curve was obtained in the range of 25–125 μg/mL for TEG and 20–100 μg/mL for URA. Specificity experiments revealed the absence of interference from excipients. The mean assay for TEG was found to be 101.4% (w/w) and for URA was 102.8% (w/w). The method was also evaluated for robustness and ruggedness, and the results obtained were satisfactory. Forced degradation studies were performed for TEG and URA in acidic and alkaline, thermal, and oxidative conditions, and no substantial degradation was observed in all the conditions. Conclusion: It is concluded that the developed stability indicating RP-HPLC method was specific, precise, accurate, sensitive, and robust for the simultaneous estimation of TEG and URA in capsules.